Prevalence of multiple sclerosis door-to-door survey in Maltepe, Istanbul, Turkey - (:unkn) unknown (KARGER, 2006)
Background: The prevalence of multiple sclerosis (MS) in Istanbul, Turkey, is unknown. We investigated the prevalence of MS in the district of Maltepe, Istanbul, Turkey. Methods: This was a cross-sectional field research study using door-to-door sampling. Maltepe is a district of Istanbul beside the sea of Marmara (population 359,298 from 2000 census). The two-phase study screened 32,531 subjects using the Poser criteria for clinical diagnosis. The chi(2) test was used for analyses of frequency distributions. Results: 33 of 32,531 people were diagnosed with MS. Their average age was 41 +/- 12.0 years (43 +/- 12.7 years for females and 37 +/- 9.6 years for males). The prevalence of MS in Maltepe was 101.4/100,000 within the total population (118.7/100,000 in the female and 76.0/100,000 in the male populations). Conclusions: The prevalence rates of MS in the Turkish population living in a district of Istanbul are considerably higher than we thought. And the prevalence rate is much higher than neighboring countries. They are similar to those recently recorded in Sicily and Germany. These figures suggest that the prevalence rate of MS is not totally dependent upon geographical variation. However, the research of our results needs to be confirmed with further investigations in order to determine the prevalence of MS in Turkey with confidence. Copyright (c) 2006 S. Karger AG, Basel
Keywords: multiple sclerosis; prevalence; Turkey; PREDICT CONVERSION; CRITERIA; SARDINIA; REGION; SPAIN